Effect of attachment flash on clear aligner force delivery: an in vitro study - Marisa Kiong; Asma Ashari; Nurul Syahira Mohamad Zamani; Reuben Axel Wee Ming How; Rohaya Megat Abdul Wahab; Alizae Marny Fadzlin Syed Mohamed; HeeJeong Jasmine Lee; Mohd Hadri Hafiz Mokhtar (BMC, 2024)
Abstract Background The introduction of auxiliaries such as composite attachment has improved the force delivery of clear aligner (CA) therapy. However, the placement of the attachment may give rise to a flash, defined as excess resin around the attachment which may affect CA force delivery. This in vitro study aims to determine the differences in the force generated by the attachment in the presence or absence of flash in CA. Materials and methods Tristar Trubalance aligner sheets were used to fabricate the CAs. Thirty-four resin models were 3D printed and 17 each, were bonded with ellipsoidal or rectangular attachments on maxillary right central incisors. Fuji Prescale pressure film was used to measure the force generated by the attachment of CA. The images of colour density produced on the films were processed using a calibrated pressure mapping system utilising image processing techniques and topographical force mapping to quantify the force. The force measurement process was repeated after the flash was removed from the attachment using tungsten-carbide bur on a slow-speed handpiece. Results The intraclass correlation coefficient showed excellent reliability (ICC = 0.96, 95% CI = 0.92-0.98). The average mean force exerted by ellipsoidal attachments with flash was 8.05 ± 0.16 N, while 8.11 ± 0.18 N was without flash. As for rectangular attachments, the average mean force with flash was 8.48 ± 0.27 N, while 8.53 ± 0.13 N was without flash. Paired t-test revealed no statistically significant difference in the mean force exerted by CA in the presence or absence of flash for both ellipsoidal (p = 0.07) and rectangular attachments (p = 0.41). Rectangular attachments generated statistically significantly (p < 0.001) higher mean force than ellipsoidal attachments for flash and without flash. Conclusion Although rectangular attachment generated a significantly higher force than ellipsoidal attachment, the force generated by both attachments in the presence or absence of flash is similar (p > 0.05).